Japan's Asian diplomacy : a legacy of two millennia - Ogura, Kazuo; Noble, David (2015)
"Japan's relations with its closest neighbors, China and Korea, are tense - exacerbated by disputes over territorial issues and the unresolved trauma of a tumultuous twentieth-century history. In this book, the author, a veteran Japanese diplomat, examines his nation's relations with its East Asian neighbors along a temporal axis stretching back some two thousand years, a perspective he feels is essential to the construction of a new Asian diplomacy. In his view, Japan's relations with China and Korea in modern times have tended to be understood within the context of Japan's relations with the West, and Japanese diplomacy has often operated as a dependent variable of the foreign policies of the Western powers. Yet as the political and economic importance of Asia seems destined to increase in coming years, the interplay of foreign policies among the Asian nations themselves should receive more of a spotlight. In order to fully appreciate Japan's place in Asia and what must be done to rebuild relations with China and Korea, an examination of the deeper patterns of historical contact among these nations serves as an essential point of departure"--Back cover.
"LTCB International Library Trust/International House of Japan."
"This book originally appeared in Japanese as Nihon no Ajia gaikō : Nisen'nen no keifu (Tokyo: Fujiwara Shoten, 2013)"--Title page verso.
Keywords: Diplomatic relations; Aussenpolitik